Textual Research on "External Kidney": With a Discussion on the Elucidation of "External Kidney" by Daoism - Xinyue ZHANG; Shujian ZHANG (Yixue yu zhexue, 2025)
The use of the term "kidneys" to refer to the male scrotum (testicles) has a long historical origin. To differentiate it from the internal kidneys, the term "external kidneys" emerged. As a fixed anatomical term, its earliest appearance was no later than the mid-Tang Dynasty, possibly originating from Buddhist or Daoist religious texts, or even earlier in the Southern Qi medical text Chu’s Medical Records. In medical literature, the term "external kidneys" generally refers to male reproductive organs, with slight variations in meaning across contexts. However, exceptions are predominantly found in Daoist texts, where the term not only shares the same usage as in medical works but also explores connections between the external kidneys and the bladder. Additionally, it is occasionally used to refer to body surface areas corresponding to "internal." While medical texts emphasize the water attribute of the external kidneys, Daoist interpretations further introduce the concept of fire, highlighting its role as a source of physiological energy.